The potential of fly ash-based geopolymers as an environmentally friendly construction material solution: A review - Mazwan, Mazwan; Fajri, Fajri (Universitas Syiah Kuala, 2024)
The use of environmentally friendly construction materials has been increasing in response to the demand for sustainable development. Fly ash-based geopolymers have emerged as an innovative and sustainable solution in the construction industry. This article discusses the potential use of fly ash-based geopolymers, covering their characteristics, synthesis process, advantages, challenges, and future development prospects. This research adopts a literature review approach, referencing various international and national journals. The study findings reveal that fly ash geopolymers possess high mechanical strength, corrosion resistance, and significantly lower carbon emissions compared to conventional concrete. This potential provides significant opportunities in supporting more environmentally friendly infrastructure development.